Impact of iceberg melting on Mediterranean thermohalinecirculation during Heinrich events - Sierro S?nchez, Francisco Javier; Hodell, David A.; Curtis, Jason H.; Flores Villarejo, Jos? Abel; Reguera Garc?a, Mar?a Isabel; Colmenero Hidalgo, Elena; B?rcena Pern?a, Mar?a ?ngeles; Grimalt, Joan O.; Cacho Lascorz, Isabel; Frigola Ferrer, Jaime; Canals, Miquel (American Geophysical Union (Washington, Estados Unidos), 2005)
En este art?culo se reconocen varios eventos que ponen en evidencia la entrada en el Mediterr?neo de agua procedente de la fusi?n de icebergs en el ?ltimo per?odo glacial y se analiza el impacto de dichos eventos en la circulaci?n profunda del Mediterr?neo Down-core samples of planktonic and benthic foraminifera were analyzed for oxygen and carbon isotopesin International Marine Past Global Changes Study (IMAGES) core MD99-2343 in order to study theinteractions between climate change in the Northern Hemisphere and the western Mediterranean thermohalinecirculation at times of Heinrich events (HE). Our results confirm the antiphase correlation between enhancedNorth Atlantic Deep Water formation and low ventilation in the Mediterranean. However, this study reveals thatthis antiphase relationship in deepwater formation between the North Atlantic and Mediterranean wasinterrupted during times of HE when the injection of large volumes of water from melting icebergs reached theentrance to the Mediterranean. These events, which lasted less than 1000 years, are represented by pronounceddecreases in both planktonic d18O and benthic d13C signals. Lower salinities of Mediterranean surface waterresulted in a slowdown of western Mediterranean deepwater overturn even though cold sea surface temperaturesand drier climate should have resulted in enhanced deepwater formation.